2014
DOI: 10.1002/jsfa.6499
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation ofSmilax chinaroot byAspergillus usamiandSaccharomyces cerevisiaepromoted concentration of resveratrol and oxyresveratrol and the free-radical scavenging activity

Abstract: Results from our study propose that bioactive components in Smilax China root were highly extracted by fermentation followed by saccharification and ethanol production, resulting in enhanced free-radical scavenging capacity. © 2013 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Piceid has structural similarity with resveratrol except for the possession of a glucose unit. It has been shown in studies that piceid provides various biological activities such as antioxidant, anti‐platelet aggregation, cardioprotective and anti‐inflammation . Quercetin, a member of the flavonoid family, is an important antioxidant component commonly consumed in diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piceid has structural similarity with resveratrol except for the possession of a glucose unit. It has been shown in studies that piceid provides various biological activities such as antioxidant, anti‐platelet aggregation, cardioprotective and anti‐inflammation . Quercetin, a member of the flavonoid family, is an important antioxidant component commonly consumed in diets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in order to measure electron reduction, the 2,2‐diphenyl‐1‐picrylhydrazyl radical (DPPH) and 2,2′‐azino‐bis‐3‐ethylbenzthiazoline‐6‐sulfonic acid (ABTS) assays were performed according to the method described previousl …”
Section: Methodsmentioning
confidence: 99%
“…The main chemical entities responsible for the various beneficial effects of SCR against AD shown in this study remain elusive. Previous studies by others have shown that SCR contains diverse categories of chemical constituents including stilbenoids, flavonoids, and steroidal saponins (Ban et al , ; Zhang et al , ; Yoon et al , ; Wang et al , ; Xu et al , ). Recent studies reported that some constituents from SCR could exert antiinflammatory activities when treated individually in various experimental models, thereby contributing to preventive and/or therapeutic effects on AD‐like skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, resveratrol has attracted increased attention owing to its benefits to human health such as protection against cancer, inflammation and oxidation . Because of the great diversity of bioactivities of resveratrol, several research studies have been carried out for increasing its concentration in plants . Actually, the concentration of polydatin (resveratrol‐3‐ O ‐β‐ d ‐glucoside) is usually far more than that of resveratrol in P. cuspidatum .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Because of the great diversity of bioactivities of resveratrol, several research studies have been carried out for increasing its concentration in plants. 10,11 Actually, the concentration of polydatin (resveratrol-3-O--D-glucoside) is usually far more than that of resveratrol in P. cuspidatum. 12 Zhang et al 13 purified a -D-glucosidase (BGL, EC 3.2.1.21) from Aspergillus oryzae sp.…”
Section: Introductionmentioning
confidence: 99%